Thermal Characterization and Heat Conductivity of Palm Kernel Shell-Based Briquettes - Enda Rasilta Tarigan; Abdul Azis Rahmansyah; Muhammad Khatami (Universitas Diponegoro, 2026)
Palm kernel shell (PKS), a major by-product of the palm oil industry, has emerged as a promising sustainable feedstock for solid biofuel briquette production. This study presents a systematic review of PKS briquettes, emphasizing their thermal properties, briquetting technologies, pretreatment methods, environmental and economic impacts, and future prospects of PKS briquettes. A PRISMA-based methodology was applied to ensure the transparent identification, screening, and synthesis of relevant peer-reviewed studies on PKS briquette production and performance. The review indicates that PKS briquettes generally possess a high calorific value, substantial fixed carbon content, and competitive combustion performance compared with other biomass fuels. Advances in densification techniques and pretreatment processes have improved the fuel quality, durability, and energy efficiency. Despite these strengths, several research gaps remain. Standardized data on thermal conductivity and heat transfer are limited, and comparative assessments with conventional fuels, such as coal and firewood, are insufficient. Moreover, inconsistencies in the experimental conditions hinder cross-study evaluation, and emission characteristics and large-scale industrial feasibility are underreported. By consolidating current findings and identifying critical knowledge gaps, this review offers a structured foundation for future research and informed policymaking, supporting the integration of PKS briquettes into sustainable energy and circular economy strategies in palm oil–producing regions